Penerapan Strategi Social Commerce dan Pengaruhnya terhadap Perilaku Pembelian Online pada Umkm di Kota Yogyakarta: Studi Kasus pada Platform Sibakul - Bambang Irjanto; Jemadi Jemadi; Bambang Sugeng D (Pusat Riset dan Inovasi Nasional, 2026)
Digitalization has transformed the pattern of interaction between businesses and consumers, one of which is reflected in the emergence of social commerce that integrates social media with online trading activities and enables two-way interaction. For micro, small, and medium enterprises (MSMEs), particularly those participating in the Sibakul Jogja platform, social commerce in practice not only functions as a promotional medium but also as a strategic tool for building trust, emotional bonding, and customer loyalty. However, the utilization of social features such as live shopping, customer reviews, and user engagement among MSMEs remains relatively suboptimal. This study focuses on analyzing the implementation of social commerce strategies in MSMEs within Sibakul, identifying the challenges encountered, and examining their influence on consumers’ online purchasing behavior. The findings indicate that Sibakul has significant potential as a region-based digital ecosystem in supporting the development of social commerce for MSMEs. Nevertheless, its effectiveness is still limited due to constraints in social features, the low digital capacity of MSME actors, and the absence of a community-based approach. These findings contribute to the development of a conceptual model and provide strategic recommendations for strengthening MSME digital marketing based on social interaction.